TOʻQIMACHILIK KORXONALARI B2B BOZORIDA QIYMAT YARATISH VA MUNOSABATLAR MARKETINGI NAZARIYASI (Marketing Journal, 2026)
AbstractThis article analysed value creation processes and the application of relationshipmarketing theory in the B2B market of textile industry enterprises. The studysystematically examined relational, added, and strategic levels of value. Key elementsof the conceptual models developed by Dwyer–Schurr–Oh, Morgan–Hunt, and Ulaga–Eggert were adapted to the textile sector. The stages of B2B relationship developmentwere identified, and the influence of trust, commitment, and information exchange on value formation was evaluated. Based on the analysis of Uzbekistan’s textile industryexport activity and international cooperation practices, directions for strengtheningrelationship capital were outlined. The research results were assessed as a practicalbasis for strengthening strategic partnerships and developing value-oriented B2Brelationships in textile enterprises.Keywords: relationship marketing, B2B market, value creation, textile industry,strategic partnership, trust, integration model.